Malignant transformation of oral submucous fibrosis: A systematic review and meta‐analysis. (9th December 2020) - Kujan, Omar; Mello, Fernanda Weber; Warnakulasuriya, Saman
Abstract: Objectives: This systematic review and meta‐analysis aimed to determine the proportion of patients who develop oral carcinomas following a diagnosis of oral submucous fibrosis (OSF) in reported longitudinal studies. We also aimed to evaluate the demographic and clinicopathological factors contributing to the progression of OSF to cancer. Methods: Individual search strategies were applied for the following bibliographic databases: MEDLINE by PubMed, Scopus, Embase, Web of Science, and Grey literature databases until August 30, 2020. Methodological assessment of the risk of bias of the included studies was undertaken using the modified Newcastle‐Ottawa scale. Meta‐analyses were conducted using a random‐effects (DerSimonian and Liard) method to calculate the pooled proportion of the malignant transformation (MT) in OSF patients. Results: Out of 585 records screened, a total of 9 observational studies were included with a total number of 6, 337 patients; of these, 292 OSF cases developed carcinomas. The pooled proportion of the MT was 4.2% (95% CI: 2.7%–5.6%) with an annual transformation rate of 0.73%. Subgroup analysis revealed that the pooled MT proportion was significantly higher among population‐based studies in comparison with hospital‐based ones ( p < .005). Most of the studies showed a high risk of bias. In several studies, there was a lack of information about the demographic and clinicopathological characteristics of OSF patients and associated risk indicators; this insufficiency in details hindered the ability to conduct further subgroup analyses. Conclusions: Despite the poorly reported and the limited number of studies, our analysis confirms that close to 4% of patients diagnosed with OSF may develop oral cancer. Cases with oral epithelial dysplasia had a higher potential for malignant transformation.